2022
DOI: 10.21037/atm-22-2103
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics combined with metabolomics analysis of the mechanism of agmatine in the treatment of septic liver injury

Abstract: Background: Acute liver injury can occur at any stage of sepsis and is an important sign of multiple organ dysfunction syndrome (MODS). Studies have shown that agmatine (AGM) can effectively improve liver injury caused by sepsis. However, due to the numerous metabolites and metabolic pathways of AGM in the human body, its mechanism in treating septic liver injury is unclear.Methods: In this study, a liver injury model of septic Sprague-Dawley rats was established by cecal ligation and perforation (CLP). After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…These results suggested that lncRNAs were primarily expressed during the 8 h period. Prior research has established that ALI may manifest at any point during sepsis, indicating its potential significance as a marker for MODS [ 58 ]. Collectively, a duration of 8 h of LPS treatment may serve as the intervention condition in the present investigation.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that lncRNAs were primarily expressed during the 8 h period. Prior research has established that ALI may manifest at any point during sepsis, indicating its potential significance as a marker for MODS [ 58 ]. Collectively, a duration of 8 h of LPS treatment may serve as the intervention condition in the present investigation.…”
Section: Resultsmentioning
confidence: 99%
“…The reference genome and gene annotation files were downloaded from genome website. The filtered reads were mapping to the reference genome using HISAT2 v2.0.5.Then, the quality of the library was evaluated by an Agilent 2100 Bioanalyzer (Agilent Technologies, Santa Clara, CA, United States).After RNA extraction, purification, and library construction of the samples, next-generation sequencing technology was used to perform paired-end (PE) testing on these libraries using the Illumina sequencing platform (NEB, United States) 14 . Then difference expression of genes was analyzed by DESeq (1.30.0) with screened conditions as follows: expression difference multiple |log2FoldChange| > 1, significant P-value < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Then difference expression of genes was analyzed by DESeq (1.30.0) with screened conditions as follows: expression difference multiple |log2FoldChange| > 1, significant P-value < 0.05. At the same time, We used R language Pheatmap(1.0.8) software package to perform bi-directional clustering analysis of all different genes of samples 14 . On the basis of the existing reference genome, using the software StringTie ( http://ccb.jhu.edu/software/stringtie/ ) to assemble the mapped reads.…”
Section: Methodsmentioning
confidence: 99%